Spectral Characteristics of Schwa in Czech Accented English - Volín, Jan; Weingartová, Lenka; Skarnitzl, Radek (Research in Language, 2013)
The English central mid lax vowel (i.e., schwa) often contributes considerably to the sound differences between native and non-native speech. Many foreign speakers of English fail to reduce certain underlying vowels to schwa, which, on the suprasegmental level of description, affects the perceived rhythm of their speech. However, the problem of capturing quantitatively the differences between native and non-native schwa poses difficulties that, to this day, have been tackled only partially. We offer a technique of measurement in the acoustic domain that has not been probed properly as yet: the distribution of acoustic energy in the vowel spectrum. Our results show that spectral slope features measured in weak vowels discriminate between Czech and British speakers of English quite reliably. Moreover, the measurements of formant bandwidths turned out to be useful for the same task, albeit less direct.